Exploring supply chain opportunities in the UK utilities sector and the supporting role of eMarketplaces - Smart, Alan (Emerald Group Publishing Limited, 2005)
Purpose - Since the privatization of UK utilities, few studies have examined supply chain management (SCM) in the sector. This paper aims to investigate the state of development of the SCM concept and the role of the emerging internet- based electronic marketplaces in supporting this. Design/methodology/approach - Using a case study method, interviews were conducted with managers in seven UK electricity and water utilities. Areas explored are the firms' supply chain priorities, how eMarketplaces can support their supply chain goals and the barriers to adoption of eBusiness solutions. Findings - The research reveals a strong orientation in both the electricity and water industry firms towards controlling cost inputs. Consequently, their focus is on managing procurement as the primary supply chain activity. The key barriers to eBusiness adoption identified are the problem of providing genuine benefits to suppliers, and the technical difficulties of marketplace implementation. Research limitations/ implications - This is an exploratory study of the domain and further work in this area needs to focus on how utilities will develop their supply chain competences and how eBusiness solutions can support them. Originality/value - The research concludes that operators of electronic marketplaces have not yet delivered a convincing case for wider participation in management of the supply chain online. A stronger SCM orientation will need to emerge in utility firms before that can occur.